2018
DOI: 10.1080/09500693.2018.1486520
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ beliefs systems about improving transfer of algebraic skills from mathematics into physics in senior pre-university education

Abstract: Senior pre-university education (SPE) students experience difficulties applying mathematics to physics. This paper reports the outcome of an online explorative quantitative study of teachers' belief systems about improving transfer of algebraic skills from mathematics into physics, conducted among 503 mathematics and physics teachers working in SPE. We used a questionnaire with 16 beliefs about improving transfer, and asked teachers to select a top 5 and distribute 50 points among them. We used agglomerative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
1
14
0
1
Order By: Relevance
“…Earlier studies on algebraic problem-solving in physics have shown (e.g., Turşucu et al, 2017Turşucu et al, , 2018b) that among students in senior pre-university education grade-10 students encounter the biggest transfer problems. Hence, we selected grade-10 physics students to gain deeper understanding in their algebraic problem-solving skills, especially their basic algebraic skills and symbol sense behavior, and whether and to which extent we could improve their problem-solving skills.…”
Section: / 24mentioning
confidence: 98%
See 4 more Smart Citations
“…Earlier studies on algebraic problem-solving in physics have shown (e.g., Turşucu et al, 2017Turşucu et al, , 2018b) that among students in senior pre-university education grade-10 students encounter the biggest transfer problems. Hence, we selected grade-10 physics students to gain deeper understanding in their algebraic problem-solving skills, especially their basic algebraic skills and symbol sense behavior, and whether and to which extent we could improve their problem-solving skills.…”
Section: / 24mentioning
confidence: 98%
“…The method to operationalize symbol sense behavior is adopted from (Turşucu et al, 2017). This means that we measured both the extent to which students demonstrated symbol sense behavior and the degree to which they applied basic algebraic skills properly during interviews.…”
Section: / 24mentioning
confidence: 99%
See 3 more Smart Citations